Detail‐preserving SPH fluid control with deformation constraints. (23rd May 2017) - Feng, Gang; Liu, Shiguang
Abstract: It is challenging to drive particle‐based smoothed‐particle hydrodynamics fluid to match the target shape and the deforming fluid shape between different models smoothly, especially when the natural fluid motion must be preserved. To achieve the desired behavior, we first generate control particles by sampling the target shapes and then apply a deformation constraint to each control particle, with its neighboring fluid particles keeping details within its influence region. For the generation of control particles, we classify input models into source object and target object, then separately sample them by voxelization method, and generate source control particles and target control particles, respectively. Our deformation constraint includes two parts. In the first part, we deform the source control model to the target control model according to specific space point correspondence between source control particles and target control particles; then, fluid particles are attracted by control particles and complete deformation between different shapes. In the second part, to reduce the lacking of fluid details when fluid deforms, we introduce a new control energy transfer mechanism for control particles. This deformation constraint is solved under smoothed‐particle hydrodynamics‐based fluid simulation framework, which makes our simulation fast, robust, and well suitable for interactive applications. Various experiments demonstrated the effectiveness of our method. Abstract : This paper proposed a novel SPH‐based fluid deformation constraint method for deforming the fluid model between different target shapes smoothly. The new method includes two parts, namely the deformation of control model and fluid detail preserving with control force transfer. For the former, it can be used to deform the control models shape and then drive fluid particles moving. For the latter, fluid detail can be preserved by this mechanism when fluid deforms. The performance of our method is efficient enough for real‐time simulation.